Optimizing the Management of Islamic Boarding School Management through the Socialization Program: A Case Study in Yayasan Persyada Nurul Haromain Surabaya - Rismawati, Rismawati; Ulfiandi, Ihsan Zikri (Abdimas Indonesian Journal, 2025)
This community service program aims to enhance the management capacity of the Persyada Nurul Haromain Foundation Surabaya through a series of socialization activities, group discussions, and technical assistance. The main problems faced by the partner include the suboptimal organizational structure, administrative management, and lack of a standardized curriculum across its pesantren branches. The implementation method used a participatory approach by involving the foundation’s board, Ahlu Syuro, and branch leaders. Data were collected through observations, semi-structured interviews, documentation, and pre- and post-socialization questionnaires. The results show a significant increase in participants’ understanding of key elements in pesantren management, task distribution, and the importance of preparing a Pesantren Revenue and Expenditure Budget Plan (RAPBP). Interactive group discussions produced a draft of a clearer organizational structure and new administrative SOPs that are more transparent and accountable. This program is expected to become an initial model for the implementation of Pesantren-Based Management (MBPP) that is adaptive, professional, and firmly upholds the value of lillahi ta’ala. Further assistance and implementation research are recommended to ensure the sustainability of pesantren governance improvements in the future.